2010
DOI: 10.5272/jimab.1522009_89
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Diagnosis of the Severe Chronic Periodontitis

Abstract: In total, 14 adult patients with severe chronic periodontitis were evaluated for the presence of associated anaerobic and aerobic bacteria. Subgingival plaque specimens from three pocket depths per patient were obtained. Microaerophilic and facultative anaerobic bacteria, probably involved in the periodontitis, were isolated in six (42.9%) patients. These were Gram negative species involving Aggregatibacter (Haemophilus) aphrophilus (14.3%), Haemophilus parainfluenzae (7.1%), Kingella denitrificans (7.1%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Revealed a positive correlation between the pocket depths and the number of Gramnegative isolates (r 2 =0.716) and negative correlation (r 2 = -0.671) between pocket depth and the number of Gram-positive isolates. (15) studied the microbiological diagnosis of the sever chronic periodontitis in which anaerobic microbiology was completed for 27 patients and found that Gram-negative anaerobic bacteria were isolated in 92.6% (25 of 27 patients), involving 90.9% of untreated patients (20 of 22 cases) and all the five treated patients. Manual instrumentation decreases the population of Gram-negative bacteria and allows for an increase in the population of Gram-positive microbes.…”
Section: Resultsmentioning
confidence: 99%
“…Revealed a positive correlation between the pocket depths and the number of Gramnegative isolates (r 2 =0.716) and negative correlation (r 2 = -0.671) between pocket depth and the number of Gram-positive isolates. (15) studied the microbiological diagnosis of the sever chronic periodontitis in which anaerobic microbiology was completed for 27 patients and found that Gram-negative anaerobic bacteria were isolated in 92.6% (25 of 27 patients), involving 90.9% of untreated patients (20 of 22 cases) and all the five treated patients. Manual instrumentation decreases the population of Gram-negative bacteria and allows for an increase in the population of Gram-positive microbes.…”
Section: Resultsmentioning
confidence: 99%
“…4,5,21 Lower prevalence rate (49.1%) was reported by Boutaga et al 14 using Real-Time PCR. On studying the microbiology of subgingival plaque samples from patients with severe chronic periodontitis, Boyanova and co-workers 22 were reported a much lower detection rate (25.9%) of P. gingivalis yielded from anaerobic culturing. However, all the mentioned references agreed on that the rate of detection is higher in disease than health.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies the presence of putative periodontal pathogens in subgingival biofi lm is signifi cantly associated with ineffective response to therapy, while the lack of subgingivally established periodontal pathogens is a criterion for a good response to therapy. 3,7,10,11,19,22,23 Moreover, it is believed that the absence of pathogens in periodontal pockets is a favourable predictor of periodontal disease compared with their presence, which is considered as a disease progression predictor. 7 Authors suggest that detection of periodontal pathogens (Aa, Pg, Pi, Cr) above certain "critical" levels after active treatment show an increased risk of recurrence.…”
Section: Indications For Microbiological Diag-nostic Tests In Chronicmentioning
confidence: 99%